Anomalous Somatosensory Cortical Localization in Schizophrenia. - Reite, Martin; Teale, Peter; Rojas, Donald C. (American Journal of Psychiatry, 2003)
Objective: Schizophrenia has been reported to be associated with altered localization of regions responding to sound in the auditory cortex, suggesting possible cortical reorganization accompanying the disorder, but it is not clear whether such disturbances are present in any primary sensory cortex other than the auditory. This study examines magnetoencephalographic localization of field sources evoked by tactile stimulation generated in area 3b of the primary somatosensory cortex in patients with schizophrenia compared with normal subjects. Method: A total of 29 subjects participated; 14 were patients with schizophrenia, and 15 were normal comparison subjects. Equivalent current dipole generators in both hemispheres were used to model the sources of the 50-msec latency somatosensory evoked field (M50) components produced by contralateral tactile mechanoreceptor stimulation of the tip of the index finger. Results: Compared with normal subjects, patients with schizophrenia demonstrated reversed asymmetry (left anterior to right) and relatively anterior and inferior displacement of the M50 equivalent current dipole location in the left hemisphere. Conclusions: Cerebral lateralization and localization of the M50 distinguished patients with schizophrenia from normal subjects. These findings suggest the possibility of anatomical displacement and/or disturbed organization of the primary sensory cortex in schizophrenia. Reprinted by permission of the publisher.